Facebook ads have a greater hold on digital marketing of Bangladesh- an observational study on wavemaker Bangladesh - Roy, Aboni (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.